(untitled) (Revista Electrónica REDINE, 2026)
Current early childhood education demands classroom management that transcends technical administration to become an ethical and pedagogical commitment to diversity. The fundamental purpose of this research was to unveil the meanings that early childhood teachers attribute to classroom management for the inclusion of children with disabilities. Methodologically, the study was framed within the interpretive paradigm with a qualitative approach, employing the phenomenological-hermeneutic method based on the postulates of Max van Manen and Dahlberg. The social actors were five teachers from the Centro Preescolar General Jacinto Lara (Barquisimeto, Venezuela), whose information was collected through open dialogic interviews and the use of field diaries. The results revealed that inclusive management is supported by essential categories such as adapted pedagogical planning, strategic organization of the learning environment, and mediating teacher leadership. The analysis through the pillars of Being, Knowing, Living Together, Undertaking, and Doing demonstrated that teaching praxis is marked by a constant tension between the ideals of inclusion and real limitations in specialized training and material resources. In conclusion, classroom management for inclusion is established as a multidimensional and deeply human phenomenon that requires ethical sensitivity and active mediation. The scientific contribution of the work lies in making visible that real inclusion does not depend solely on legal frameworks, but on an articulated management that transforms school culture and values diversity as a central axis of integral development.